Effect of Garlic (Allium sativum L.) and Ginger (Zingiber officinale Roscoe) Mixtures on Performance Characteristics and Cholesterol Profile of Growing Pullets - Bamidele , O.; Adejumo, I.O. (International Journal of Poultry Science, 2012)
Animal products, especially poultry products are relatively affordable and accessible sources of protein in human diets. However, the risk of cholesterol accumulation in the blood stream as well as its associated diseases has placed a constraint on the consumption of poultry products. Cholesterol aids metabolic and biochemical functions of the body but is potentially unhealthy at increased levels. Dietary therapy has been recommended as a major remedy for cardiovascular diseases as well as other cholesterol-related diseases. Hence, the study assessed the combined effect of garlic and ginger mixtures on the cholesterol profile of growing pullets. The results of the study revealed that garlic and ginger mixtures at the supplemented levels significantly (p0.05) effect on growth performance and is also considered non toxic as shown by the White Blood Cell (WBC) count. The experimental diets containing 1.00% garlic and 0.50% ginger mixtures and 2.00% and 0.75% ginger mixtures had the best results for total cholesterol and LDL cholesterol of the growing pullets.